Peningkatan Bantuan Keuangan APBD Kabupaten/Kota Dalam Mendukung Kinerja Pemerintah Kota Surabaya Di Provinsi Jawa Timur - Suyanto (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Basically economic development is an effort to increase capacity and freedom of choice. The creation of economic development is very dependent on the role of the government which is reflected in government spending. The ability of local governments to manage finances as outlined in the